In vitro and in vivo biocompatibility study of folate-lysine-PEG-PCL as nanocarrier for targeted breast cancer drug delivery. (June 2018) - Zamani, Mostafa; Rostamizadeh, Kobra; Kheiri Manjili, Hamidreza; Danafar, Hossein
Graphical abstract: Highlights: FA-L-PEG-PCl synthesized by new method that did not need DMSO as solvent. Our synthesized copolymers had great in vivo and in vitro biocompatibility. Addition of folate receptor to NCs causes to significant enhancement in TMX anticancer activity. In addition, the drug release in pH 5.5 was higher than pH 7.4 that is suitable for drug delivery in cancer. Small size of drug loaded-NCs and their stability can help to accumulate drugs in tumor site. Abstract: Amphiphilic FA-L-PEG-PCL (PEG: Poly ethylene glycol-hydrophilic segment, FA: Folic acid-targeting agent, L: Lysine-linker, PCL: Poly caprolactone-hydrophobic segment) copolymer was synthesized. Proton nuclear magnetic resonance (HNMR), Fourier-transform infrared spectroscopy (FT-IR), Dynamic light scattering (DLS), atomic force microscopy (AFM), dynamic scanning colorimetry (DSC) were used for characterization of synthesizes copolymers. For determining cytotoxicity of our copolymers, we used from MTT assay, Hemolysis assay and lethal dose 50 (LD50) test. These tests revealed that copolymers had least in vitro and in vivo cytotoxicity and they are categorized as practically none toxic. These copolymers were self-assembled into Round-shaped folate-functionalized micelles in aqueous medium for the folate receptor (FR)-mediated targeted delivery of Tamoxifen (TMX)-the anticancer drug- to cancer cells. The drug loading capacity and in vitro pH responsive controlled release performance showed that these micelles had potential as drug delivery systems (DDS) for hydrophobic anti-cancer drugs such as TMX. FA-L-PEG-PCL micelles was non-cytotoxic in high concentrations. Loaded-TMX micelles obviously showed an increase in killing of the cancer cells.